Processo de reassentamento no Conjunto Habitacional Nova Vila da Barca em Belém/Pa - AMORIM, Raquel da Silva (Universidade Federal do Pará, 2013)
This work focuses on the dynamics of families who have experi enced the process of resettlement housing project in an area of social stilts in the town of Belem/PA, called Vila da Barca. This area was the object of urban intervention performed by the municipal government funded by the federal government‘s resource CAIXA. We seek to contextualize the dynamics of the occupation process of capitalist cities, to reveal the peculiarities of the city in Brazil, the Amazon and specifically in Belem. The interest by the object now searched if game to our everyday observations in Belem. Our investigation was based on a perspective-dialectic and was operated by a bibliographic and documentary, followed by the field work, based on interviews and direst observations. The survey (search) results highlight the changes in the dynamics of families who have suffered the urbanistic and social intervention and changes in their way of living (live) caused by the process of resettlement for housing new town of Barca.